Technopreneurship : conceptualised - Kakawa, Nicholas (Deurchland : Lap Lambert Academic Publishing, 2012)
This book endeavours to conceptualise technopreneurship as a course. It represents the preliminary knowledge gathered around the course.
Introduction -- Defining technopreneurship -- Technopreneurship applied -- Technology -- High-tech -- Entrepreneurship -- A framework for launching a high-tech venture -- Innovation defined -- Sources of innovation -- Economic conception of innovation -- Principles of innovation -- Diffusion of innovation -- Factors influencing innovation
Includes bibliographical references.
Keywords: TECHNOPRENEURSHIP